1987
DOI: 10.1029/ja092ia01p00213
|View full text |Cite
|
Sign up to set email alerts
|

Spectral studies of the sources of ionospheric electric fields

Abstract: Spectral analyses have been performed upon a number of incoherent scatter radar data sets obtained at Jicamarca, Peru; Chatanika, Alaska; and Arecibo, Puerto Rico, with the goal of understanding the sources of electric fields with periods in the range of 1–10 hours. Two distinct sources are identified and studied in some detail. In quiet times, atmospheric gravity waves seem the most likely source of the ionospheric electric field. In fact, both in an average sense and in the single case study available the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 26 publications
8
73
0
Order By: Relevance
“…In our knowledge, there is only one documented event of similar quasi-periodic electric ®eld¯uctuations of eastward polarity at the nightside (22-04 LT) dip equator. This event of February 17±18, 1976, studied by Gonzales et al (1979) as well as Earle and Kelley (1987), is characterised by¯uctuations with signi®cant power at »1 h period in IMF B z as well as in electric ®elds at auroral and dip equatorial stations. But this event too does not seem to be of DP2 origin because the day-tonight polarity of the equatorial electric ®elds (eastward on nightside and westward on dayside) is at variance with the theoretical pattern of DP2 electric ®elds.…”
Section: Resultsmentioning
confidence: 99%
“…In our knowledge, there is only one documented event of similar quasi-periodic electric ®eld¯uctuations of eastward polarity at the nightside (22-04 LT) dip equator. This event of February 17±18, 1976, studied by Gonzales et al (1979) as well as Earle and Kelley (1987), is characterised by¯uctuations with signi®cant power at »1 h period in IMF B z as well as in electric ®elds at auroral and dip equatorial stations. But this event too does not seem to be of DP2 origin because the day-tonight polarity of the equatorial electric ®elds (eastward on nightside and westward on dayside) is at variance with the theoretical pattern of DP2 electric ®elds.…”
Section: Resultsmentioning
confidence: 99%
“…The data thus correspond to bottomside F layer and under non-ESF conditions. The time rate of change of phase path (APIAt) during the evening hours is primarily a measure of vertical plasma motion near the reflection level as the contribution due to electron density changes below the reflection level is negligible at such times (e.g., Georges, 1967). The vertical drift, V. of the reflection level is then 0.5 (AP/At) which, at and near the dip equator, represents the combined effect of electromagnetic (EXB) drift and an apparent upward drift due to chemical loss.…”
Section: Data and Analysismentioning
confidence: 99%
“…Earle and Kelley (1987) identified atmospheric waves and magnetospheric electric fields as the most likely sources of equatorial zonal electric field variations in the range 1-10 hr during quiet and disturbed periods respectively. Nair et al (1992) and Subbarao and Krishnamurthy (1994) suggested the frequently occurring medium scale gravity waves as the source of shorter period (<1 h) variations of V. in the evening period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical estimates of this time scale (discussed in section 2.4) depend on the spatial scale of the phenomenon of interest, ranging from a few seconds for purely ionospheric events to 15-30 min for changes on scales of magnetospheric dimensions. The latter is the approximate time scale for many observed important M-IT processes, such as substorms and magnetospheric transients [e.g., Earle and Kelley, 1987;Ginskey, 1993, 1995;Zesta et al, 2000;Bristow et al, 2003;Huang et al, 2008Huang et al, , 2010; the focus of our paper is on time scales from a few minutes to 20-30 min. It is, thus, not surprising that, as pointed out by Schunk [2013], conventional ionospheric quasisteady state equilibrium models, e.g., thermosphere ionosphere electrodynamics global circulation model [Richmond et al, 1992], coupled thermosphere ionosphere plasmasphere electrodynamics model [Fuller-Rowell et al, 1996], and the global ionosphere-thermosphere model (GITM) [Ridley et al, 2006], describe well the large-scale slow variations or "climatology" of the ionosphere-thermosphere system but do not work well for the rapidly changing phenomena or "weather."…”
Section: Introductionmentioning
confidence: 99%